New Sacred Places in Contemporary Poland: Ethnographic Case Study of Two Miracles in Sokółka and Legnica - Kalniuk, Tomasz (Journal of religion in Europe, 2021)
Abstract Events that happened in Poland in 2008 and 2013 related to the alleged miracles in Sokółka (in the Podlasie region) and Legnica (in the Silesia region) seriously affected the native ‘sacrosphere.’ Sensational information about the unusual events polarized public opinion by confronting secular and religious worldviews. At the same time, the increase in the devotion of the faithful was accompanied by folklore-forming mechanisms, adding new threads to the ‘miraculous story.’ Ethnographic research performed in the newly founded sanctuaries reveals elements of sensuality specific to folk religiosity. Miracles displaying the motif of blood build the reputation of Sokółka and Legnica as new holy places, attracting pilgrims and tourists from Poland and abroad. Contrary to pessimistic predictions of widespread secularization, there was a revival of the so-called ‘traditional piety.’ Folk religiosity revealed its vitality.